The One and the Many: Joshua Ferris's Then We Came to the End. Issue 3 (27th May 2018) - Russell, Alison
ABSTRACT: As a post-9/11 office novel, Joshua Ferris's Then We Came to the End effectively represents the contemporary American work novel's anxieties about violence, trauma, and loss—particularly the loss of the American Dream—and its consolations in humor and human community. The novel's distinctive first-person plural narration foregrounds Ferris's understanding of office workers' need for safety in numbers and for social connectedness, even while they hope that their individual achievements will be rewarded and save their jobs. The tension between the desire for individualism and also for group identity signals a shift in workplace fiction from earlier incarnations, reflecting the changed environment of the American office place. By focusing on the advertising business and its language manipulations, Ferris ultimately asks whether or not words—and work—can still matter or create meaning.